2014
DOI: 10.3329/bjp.v9i3.18874
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of aqeous methanolic extract of <i>Rumex dentatus</i> in paracetamol induced hepatotoxicity in mice

Abstract: Rumex dentatus is well known plant of Polygonaceae family which is widely used in traditional medicine to treat gastrointestinal tract. R. dentatus at doses 250 and 500 mg/kg significance decreased (p<0.001) the elevated level of ALT, AST, ALP and bilirubin induced by paracetamol and results are comparable (p<0.001) with silymarin. The results were supported by histopathological investigations, phytochemical screening and detection of hepatoprotective active constituents e.g quercetin, kaempferol, myricetin by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…The current data indicated that treatment of HCC group with R. vesicarius extract elicited significant reduction in serum AST, ALT, ALP and γ-GT activity relative to the untreated HCC group. These results are in agreement with Chen (2010) and Saleem et al (2014) who reported that R. dentatus significantly controlled the elevation of liver enzymes. This hepatoprotective action is possibly ascribed to the presence of many active constituents.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current data indicated that treatment of HCC group with R. vesicarius extract elicited significant reduction in serum AST, ALT, ALP and γ-GT activity relative to the untreated HCC group. These results are in agreement with Chen (2010) and Saleem et al (2014) who reported that R. dentatus significantly controlled the elevation of liver enzymes. This hepatoprotective action is possibly ascribed to the presence of many active constituents.…”
Section: Discussionsupporting
confidence: 93%
“…Photomicrograph of liver tissue section of HCC group treated with R. vesicarius extract showed very few inflammatory cells infiltration in the hepatic parenchyma. In accordance of our results Saleem et al (2014) reported that animals treated with aqueous methanolic extract of R. dentatus showed almost normal hepatocytes and normal structural organization of the liver.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, various important bioactive compounds, such as chlorogenic acid, quercetin, myricitin, vitamin C, and kaempferol, have been identified in these roots. Saleem et al (2014) demonstrated hepatoprotective effect of R. dentatus against paracetamol-induced liver damage in mice. Given the medicinal importance of R. dentatus , the purpose of the present study was to investigate it for possible anticancer activity, using the MDA-MB-231 breast cancer cell line.…”
Section: Introductionmentioning
confidence: 93%
“…The aerial and roots parts of different plants belong to the Polygonaceae family, including Rumex , have been used as a natural source of traditional medicines in several therapeutic uses, such as anti-inflammatory, antioxidants, antianalgesic, and antimicrobial activities [ 10 , 11 ]. They are also used for the treatment of certain diseases like cancer, tumor, and diseases related to liver and urinary/kidney functions [ 12 , 13 ]. There are some reports in the literature about the evaluation of some species of Rumex which have exhibited health-promoting effects and have been used as traditional foods and herbal remedy.…”
Section: Introductionmentioning
confidence: 99%